Effect of Family Support on Psychological Disorders in Pregnant Women in Pulo Lor Village, Pulo Lor District, Jombang Regency - Pitriawati, Dewi; Srirahandayani, Dwi; Grah Prihartanti, Niken; Rosmaharani, Shanti (PT. Riset Press International, 2024)
Psychological health disorders during pregnancy can cause poor pregnancy outcomes in the form of complications including the risk of preterm labor, delays in the delivery process, low birth weight, hypertension and impaired fetal neurodevelopment and development. The risk of these complications can be reduced by improving the factors that affect the psychological health of pregnant women including interpersonal relationships, family roles and social support. The purpose of this study was to determine the effect of family support on the psychological health status of pregnant women using the unpaired categorical analytic research method of more than two groups with univariate, bivariate and multivariate data analysis. The research process carried out on pregnant women in Jombang Regency has found that influential family support can reduce the risk of psychological disorders in the form of anxiety during pregnancy.